The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.1021/acs.chemmater.9b01263
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Interlayer Space on the Water Oxidation Performance in a Family of Surfactant-Intercalated NiFe-Layered Double Hydroxides

Abstract: Layered double hydroxides (LDHs) are low dimensional materials that act as benchmark catalysts for the oxygen evolution reaction (OER). Many LDH properties affecting the OER have been studied to reach the optimal efficiency but no systematic studies concerning the influence of the interlayer space have been developed. In this context, these materials allow a large tunability in their chemical composition enabling the substitution of the interlayer anion and therefore modifying exclusively the basal space. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
69
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 81 publications
(82 citation statements)
references
References 58 publications
5
69
0
Order By: Relevance
“…In order to allow for the insertion of APTES moiety and induce the covalent grafting, a previous enlargement of the basal space is mandatory. For this purpose, the incorporation of more labile dodecyl sulphate (DS) molecules (DS‐intercalated LDH) by anion exchange reaction is carried out prior to the final inclusion of APTES (Scheme ) . In addition, it is demonstrated that the organophilicity increases after the DS intercalation, hence favoring the insertion of the smaller APTES molecules into the interlayer space and their condensation with the ‐OH groups found on the LDH surface.…”
Section: Resultsmentioning
confidence: 76%
See 3 more Smart Citations
“…In order to allow for the insertion of APTES moiety and induce the covalent grafting, a previous enlargement of the basal space is mandatory. For this purpose, the incorporation of more labile dodecyl sulphate (DS) molecules (DS‐intercalated LDH) by anion exchange reaction is carried out prior to the final inclusion of APTES (Scheme ) . In addition, it is demonstrated that the organophilicity increases after the DS intercalation, hence favoring the insertion of the smaller APTES molecules into the interlayer space and their condensation with the ‐OH groups found on the LDH surface.…”
Section: Resultsmentioning
confidence: 76%
“…Taking this into account, it is expected that the reversibility of silane bonding should not affect the electrocatalytic behavior of NiFe‐LDHs . In this context, we tested the oxygen evolution reaction (OER) electrocatalytic performance of NiFe‐AQ and NiFe‐APTES in a basic medium (1 m KOH) in a standard three‐electrode cell (Figure and Table ).…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Taking into account that the nature of the interlayer anion (i. e., size, hydrophobicity, acidity, etc.) can influence the electrochemical properties, a systematic study exploring the supercapacitive performance with the progressive increase of the basal space would be desirable.…”
Section: Introductionmentioning
confidence: 99%